UNniversalisme Islam sebagai Perwujudan Agama Rahmatan lil 'Alamin (Analisis terhadap Konsep Universalisme Islam Nurcholish Madjid) - Widasari, Rizka Wenda; , Drs. Suharjianto, M.Ag (2016)
Islam is the last divine religion which has been revealed to complete the teachings of previous religions. Islamic teachings encompass various commands and prohibitions neither limited by space nor time; so its teachings are valid from the time it revealed until the end of time, without any limitation of certain people or nation. That's why Islam is very interesting to study by its adherents, as well as others. Nurcholish Madjid is one of the figures in this country who has a tendency in concerning Islamic studies. Islam Universalism is a Nurcholish idea that is questioned for using suffix "ism". This research is questioning Islam Universalism concept offered by Nurcholish and its correlation to Islam as rahmatan lil'alamin religion. This study aimes to find answers to Islam Universalism from Nurcholish Madjid perspective, as well as the correlation between Islam Universalism and Islam rahmatan lil'alamin religion. This is a literature study, as the data is taken from the collected works, writings, and texts. The approach is a qualitative-historical-philosophical one, because such theories and ideas are taken from Nurcholish writings in the past. Meanwhile, the analysis of research is conducted after documentaries data collection using descriptive analysis, namely by reducing data, presenting it, and then drawing conclusions from the data that have been discovered. Further, Islam Universalism of Nurcholish Madjid has no significant difference with the concept of Islam as a rahmatan lil 'alamin religion. Because there are three things standing out of ideas: (1) the meaning of the word Islam means submission-which is a human nature; (2) Islam is revealed for the prosperity of the earth, by providing rules to men as God's representatives; (3) the context of Islamic teachings are not limited to space and time.